2001
DOI: 10.1016/s0885-3924(01)00277-9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Affective State and Quality of Life of Chemotherapy Patients Who Do and Do Not Develop Chemotherapy-Induced Oral Mucositis

Abstract: The purpose of this longitudinal study was to compare the quality of life and affective state of patients receiving chemotherapy who developed oral mucositis to patients who did not. Outpatients had their mouths assessed at the beginning of their chemotherapy, completed the Multidimensional Quality of Life scale, Cancer version (MQOLS-CA) and the Profile of Mood States (POMS). Patients again completed the MQOLS-CA and POMS if they developed mucositis during their three cycles (monthly), or if they did not and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
1
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 24 publications
2
62
1
8
Order By: Relevance
“…7,10,11 The literature indicates that 46% of patients with OM report 3 to 4 simultaneous OMrelated dysfunctions. 12 The HQoL was severely compromised for patients with OM, 11,13,14 especially in the functional sphere. 11 Patients with cancer have always identified OM as 1 of the major troubling symptoms and the primary cause of distress in their cancer treatment.…”
mentioning
confidence: 99%
“…7,10,11 The literature indicates that 46% of patients with OM report 3 to 4 simultaneous OMrelated dysfunctions. 12 The HQoL was severely compromised for patients with OM, 11,13,14 especially in the functional sphere. 11 Patients with cancer have always identified OM as 1 of the major troubling symptoms and the primary cause of distress in their cancer treatment.…”
mentioning
confidence: 99%
“…In addition to such common side effects as nausea 1 and fatigue, 2 many patients experience heightened emotional distress 3,4 and interference with physical, social, and role functioning 5 as a consequence of receiving chemotherapy. Although much of the effort to improve quality of life has focused on the evaluation of pharmacologic agents, such as antiemetic medications, 6 a number of randomized clinical trials have documented the benefits of psychosocial interventions for patients undergoing chemotherapy treatment.…”
mentioning
confidence: 99%
“…After reviewing titles and abstracts, 14 studies were identified as potentially relevant. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Reasons for exclusion (Table 2) 13-26 were quantitative study design and inadequate focus. Finally two studies 27,28 were included.…”
Section: Resultsmentioning
confidence: 99%